Phytonyms in Russian, Chinese and Korean Linguistic Cultures - Han, Yuehao (Bulletin of Yerevan University H: Russian Philology, 2024)
The study of phytonyms in Russian, Chinese and Korean linguistic cultures is a comprehensive comparative analysis aimed at identifying common and specific features in the names of the flora of these languages. This work aims at a comprehensive analysis of the influence of natural and climatic conditions, cultural traditions, worldview and mentality of native speakers on the formation of phytonyms in these linguistic cultures. The structure of the study includes a detailed review of phytonyms in each of the languages under consideration, an analysis of the features of their use in linguistic practice and symbolic significance in the culture of the corresponding ethnic group. Special attention is paid to identifying universal and unique features in plant names due to the specifics of the natural environment, economic activity, religious beliefs, mythology and folklore. The conclusions of the work emphasize the need for further in-depth study of phytonyms in the language system and in the cultural context, since this lexical group is a valuable source of information about the worldview, value orientations and cultural dominants of the ethnic group. The results of the study show that phytonyms can express not only the real, objective characteristics of plants, but also associative, culturally determined meanings reflecting the specifics of the national mentality and worldview. The results obtained can be applied in the theory and practice of intercultural communication, in teaching Russian, Chinese and Korean as foreign languages, as well as in lexicographic practice in compiling specialized dictionaries of phytonymic vocabulary.